The preparation of α-oxo acid derivatives suitable for specific-radioactivity determination - Mowbray, J. (1970)
1. Conditions favouring the condensation of o-phenylenediamine with α-oxo acids to form substituted quinoxalines have been investigated. The best yields (85–100%) are obtained by incubation of the reagents in 2m-hydrochloric acid. Substitution of acetic acid for hydrochloric acid, or of halogen-substituted 1,2-diaminobenzenes for phenylenediamine, increases the initial rate of reaction, but not the yield of quinoxalines. 2. The quinoxaline derivatives are insoluble in water and can be readily purified. They are very suitable for determination of the specific radioactivities of radioactively labelled α-oxo acids because they are colourless, soluble in dioxan-based scintillators, and their strong absorption of u.v. light facilitates their chemical determination. As little as 1 nmol can be accurately determined by means of the blue fluorescence produced by absorption of light at 340–360nm. 3. Optimum conditions for preparation, purification and separation by paper and thin-layer chromatography are described.